Spatial Distribution of Sulphur and its Relationship with Soil Attributes under Diverse Agro-climatic Zones of West Bengal, India - Gora Chand Hazra, Dipa Kundu, Biplab Pal; S.K.P. Ghouse, Shreya Das, Rubina Khanam Animesh Ghosh Bag*, Nitin Chatterjee (Journal of the Indian Society of Soil Science, 2022)
This investigation is aimed to conduct a delineation study to know the spatial distribution of available sulphur (S) in different agro-climatic zones and their influencing soil factors. Geographical information system (GIS) is an important tool to identify the S deficient sites. In this study, Arc Info GIS has been used to prepare the spatial distribution maps of available S in the soil of different districts. For this, grid-based detailed block-wise soil sampling has been carried out during 2017-2019 in long-term crop-growing fields from ten (Darjeeling, Alipurduar, South Dinajpur, Malda, Murshidabad, Nadia, Bankura, Purulia, Birbhum and East Midnapore) districts of West Bengal, India, belonging to six different agro-climatic zones. Spatial distribution maps (1:50000) show that available S highly varies from one agro-climatic zone to another zone. The results showed that available S content was highest in the terai zone (20.28 ± 8.00 mg kg-1) followed by the northern hill zone (11.09 ± 5.54 mg kg-1) and old alluvial zone (10.39 ± 6.8 mg kg-1). The lower available S was found in areas under the red and laterite zone (6.47 ± 4.29 mg kg-1). This study concluded that available S status is low to deficient for red and laterite and coastal saline zones, which differs from hill and terai zone. Organic carbon content and silt content exerted a positive correlation (r = 0.79 and 0.78, respectively) with available S.